MANGATASI PERILAKU MEMBOLOS MELALUI KOMSELING INDIVIDU DENGAN MENGGUNAKAN PENDEKATAN BEHAVIOR TEKNIK SELF MANAGEMENT PADA PESERTA DIDIK KELAS XI ANIMASI SMKN 4 KOTA MADIUN SEMESTER 1 TAHUN PELAJARAN 2024/2025 - Lazuardi Enggar Priambodo; Rischa Pramudia Trisnani; Martina Dhyastuti (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Skipping behavior is a phenomenon occurring at SMKN 4 Madiun. According to data obtained by researchers, this phenomenon is most commonly found in the XI Animation class, based on data collected during the first semester of the 2024/2025 academic year. There are 5 students with the highest skipping rates compared to other students. This study aims to determine whether individual counseling using self-management techniques can address skipping behavior among students in the XI Animation class at SMKN 4 Madiun, who exhibit high levels of skipping behavior. The selection of subjects was based on pre-test questionnaires indicating high skipping rates among students. The pre-test results revealed 5 students with high skipping rates, identified as FY, LU, KF, BR, and GH. After implementing behavioral counseling services using self-management techniques, these 5 students showed post-test results indicating a decrease in skipping rates. Their skipping behavior fell into the low category. Based on the pre-test and post-test results, it can be concluded that there was a behavioral change after individual counseling using self-management techniques. Initially exhibiting high skipping rates, the students' behavior shifted to low skipping rates.